2016
DOI: 10.18632/aging.100897
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D ligands mediate immunosurveillance of senescent cells

Abstract: Cellular senescence is a stress response mechanism that limits tumorigenesis and tissue damage. Induction of cellular senescence commonly coincides with an immunogenic phenotype that promotes self-elimination by components of the immune system, thereby facilitating tumor suppression and limiting excess fibrosis during wound repair. The mechanisms by which senescent cells regulate their immune surveillance are not completely understood. Here we show that ligands of an activating Natural Killer (NK) cell recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
187
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(196 citation statements)
references
References 59 publications
(106 reference statements)
2
187
0
Order By: Relevance
“…The SASP, composed of pro‐inflammatory cytokines, chemokines, growth factors, and proteases, can modulate the senescent cell's microenvironment and promote its interaction with the immune system (Coppe et al , ; Lujambio et al , ; Sagiv & Krizhanovsky, ; Sagiv et al , ). We found that compared to 2‐day cultures, our trophoblast cultures on day 5 indeed exhibited significantly upregulated gene sets associated with the immune response, cytokine activity, and major signaling pathways regulating the SASP, including JAK‐STAT and MAPK (Fig D).…”
Section: Resultsmentioning
confidence: 99%
“…The SASP, composed of pro‐inflammatory cytokines, chemokines, growth factors, and proteases, can modulate the senescent cell's microenvironment and promote its interaction with the immune system (Coppe et al , ; Lujambio et al , ; Sagiv & Krizhanovsky, ; Sagiv et al , ). We found that compared to 2‐day cultures, our trophoblast cultures on day 5 indeed exhibited significantly upregulated gene sets associated with the immune response, cytokine activity, and major signaling pathways regulating the SASP, including JAK‐STAT and MAPK (Fig D).…”
Section: Resultsmentioning
confidence: 99%
“…It is thought the clearance of senescent cells can result from the activity of both adaptive and innate immunity; the latter resulting from the increased expression of ligands (e.g. NKG2D) on senescent cells that target them for selective killing by natural killer (NK) lymphocytes (Sagiv et al, 2016). Therefore, mechanisms to augment cellular immunity or NK function might be therapeutically beneficial in some settings.…”
Section: Translating Senescencementioning
confidence: 99%
“…Drug‐induced transcription of MICA and PVR genes involves the transcriptional factor E2F and is dependent on the cellular redox state . Notably, NKG2D and DNAM‐1 ligands have been shown to be expressed by senescent cells and drug‐induced senescent tumor cells, unmasking an important role of NK cells for the immune surveillance of senescent cells …”
Section: Introductionmentioning
confidence: 99%